Remazol Briliant Blue Uptake by Green and Low-Price Black Carbon from Ilalang Weeds (Imperata cylindrica) Activated by KOH Solution - Ngatijo Ngatijo; Edwin Permana; Lusi Pitri Yanti; Bayu Ishartono; Rahmat Basuki (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Synthesis of activated carbon (AC) from green, low-price, and renewable source as a pollutant adsorbent is growing interest of researcher. This work aims to synthesis of AC from Ilalang weed (Imperata cylindrica) (IW-AC) with KOH activator as a green and low price Remazol Brilliant Blue dye (RBB) adsorbent. The success IW-AC synthesis was evidently characterized by Fourier Transform-Infrared (FT-IR) and Scanning Electron Microscopy (SEM). The effects of initial solution pH, adsorbent dosage, initial RBB concentration, and contact time were systematically investigated. Results showed the optimum condition of RBB adsorption was occurred at low pH (2.0-4.0) and 75 mg of adsorbent dosage. Under the optimum condition, the equilibrium adsorption data fitted well to the Langmuir isotherm with the adsorption capacity of RBB uptake was 13.42 mg/g. Calculation of adsorption energy by Dubinin-Radushkevich (D-R) isotherm model (13.39 kJ/mol) showed that the electrostatic interaction was the main interaction of RBB adsorption on IW-AC. Adsorption kinetics showed that the adsorption behavior followed the Ho pseudo-second-order kinetic model. The experimental results of this work demonstrate that the IW-AC can be used as a promising green and low-cost adsorbent for removal of anionic dyes from aqueous solution.